The Concept of Ecotheology in the Qur'an: Reinterpretation of QS. Yusuf [12]: 43-49 Through Ma’nā-cum-Maghzā Approach - Rafli Rahman; Abdul Muiz Amir; Akbar Haseng; Muhammad Hasdin Has (Sao Literasi Publisher, Yayasan Pendidikan Khaerul Munif, 2025)
This study reveals that QS. Yūsuf [12]:43-49, which has been understood as a historical narrative, contains ecological concepts that are highly relevant to the current global environmental crisis. In the story of the king's dream, interpreted by the Prophet Yusuf, about seven years of abundance followed by seven years of famine, there is a lesson about the importance of sustainability strategies in managing natural resources. This study uses a ma'nā-cum-maghzā approach to interpret the historical meaning of the verse with contemporary issues such as sustainability and climate change. The results of the study show that this verse offers practical solutions in facing the ecological crisis, with an emphasis on the importance of balance between the utilisation and preservation of nature. This study enriches the discourse on Islamic ecotheology, which was previously limited to normative understanding, by providing a more in-depth and applicable interpretation. Its practical contribution is to encourage Muslims to adopt ecological principles in their daily lives and public policies that support sustainability. Further research could explore the application of ecological concepts in global policies, particularly those related to climate change mitigation and sustainability.